Epidemiological Review of Injuries in Rugby Union - Jean-François Kaux; Marc Julia; François Delvaux; Jean-Louis Croisier; Bénédicte Forthomme; Damien Monnot; Marie Chupin; Jean-Michel Crielaard; Caroline Le Goff; Patrick Durez; Philippe Ernst; Sébastien Guns; et al. (MDPI AG, 2015)
Rugby is a sport that is growing in popularity. A contact sport par excellence, it causes a significant number of injuries. In Rugby Union, there are 30 to 91 injuries per 1000 match hours. This epidemiological review of injuries incurred by rugby players mentions the position and type of injuries, the causes, time during the match and season in which they occur and the players' positions as well as the length of players' absences following the injury.